Atherosclerotic carotid disease and cardiovascular risk in HIV-Infected patients - Hueb, J. C. [UNESP]; Salmazo, Péricles [UNESP]; Barbosa, Alexandre Naime [UNESP]; Terribilli, R. [UNESP]; Matsubara, B. B. [UNESP] (BMJ, 2013)
Introduction Although survival has been improved in HIV-infected patients, the risk for atherosclerotic diseases has increased. Objective To evaluate the effect of HIV infection on atherosclerosis in asymptomatic patients. Subjects and methods Study design: observational, prospective case-control study, including 124 consecutive male and female HIV-infected patients, older than 18 year (HIV-group). Results were compared with 130 healthy volunteers of same gender and age (Control-group). Study protocol: Clinical evaluation followed by ultrasound exam of carotids for carotid intimal-medial thickness (CIMT) measurement. The presence of atherosclerosis plaques was recorded. Statistical analysis: Chi-square test and linear regression analysis. Significance level: p < 0.05. Result Age (HIV-group:43.87 ± 11.31 vs Control-group: 42.9 ± 11.54, p = 0.324) was similar in both groups. There was 52.00% male in HIV-group and 54.00% in Control group. Atherosclerotic plaque was identified in 30.64% of the patients HIV and in 3.84% of the control (p < 0.001). Surprisingly, 22% of HIV-infected patients, classified at low risk score Freminghan, presented plaques in the carotid arteries. For controls, there was an increase of 0.068 mm in the CIMT for each one-year increase in age (OR: 1.068; CI95%: 1.03–1.107; p < 0.001). The presence of HIV increased this increment for tenfold (OR: 10.7; CI95%: 3.58–31.76; p < 0.001). There was an interaction between age and HIV-infection to increase CIMT (p < 0.001). Conclusions Our results indicated that: 1- patients with HIV are at higher risk for atherosclerosis in the carotid artery than control individuals. 2- The effect of age on risk for atherosclerosis occurs in both groups, however it is more remarkable in HIV-infected patients.